Trends in Corporate Energy Strategy of Russian Companies - Tryndina, Nikol; Moiseev, Nikita; Lopatin, Evgeniy; Prosekov, Sergey; Kejun, Jiang (International Journal of Energy Economics and Policy, 2019)
This paper proposes to the analysis of Russia's energy strategy, with respect to the interconnection of governmental strategy concerning energy extraction, reproduction and distribution and corporate energy strategies. The current trends in Russian energy strategy have been studied on the back ongoing processes in Russian corporate energy strategy formulation, with the use of statistical analysis of total volume of energy generated over the period from each source. The conclusions on areas for development and key drivers of corporate energy strategy have been made. Keywords: energy, Russian energy strategy, corporate energy strategy, energy efficiency JEL Classifications: C30, D12, Q41, Q48 DOI: https://doi.org/10.32479/ijeep.8644